2012
DOI: 10.3945/ajcn.111.021915
|View full text |Cite
|
Sign up to set email alerts
|

Fish-oil supplementation enhances the effects of strength training in elderly women

Abstract: Strength training increased muscle strength in elderly women. The inclusion of FO supplementation caused greater improvements in muscle strength and functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
245
9
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(286 citation statements)
references
References 32 publications
15
245
9
4
Order By: Relevance
“…While we originally hypothesized that anti-inflammatory effects of v-3 supplementation would be the underlying mechanism, we did not observe any statistically significant changes in systemic inflammatory markers, such as hs-CRP and IL-6, although levels of several other chemokines were improved in response to the intervention as previously reported (9). It is possible that the effects of v-3 fatty acids on protein turnover are independent of its effects on inflammatory pathways, as suggested in previous studies (4,20). Since we hypothesized that the beneficial effects would be mediated though inflammatory pathways, lower CRP concentrations in the intervention arm at baseline could have led to a reduced effect of fish oil supplementation on protein breakdown.…”
Section: Discussionsupporting
confidence: 62%
“…While we originally hypothesized that anti-inflammatory effects of v-3 supplementation would be the underlying mechanism, we did not observe any statistically significant changes in systemic inflammatory markers, such as hs-CRP and IL-6, although levels of several other chemokines were improved in response to the intervention as previously reported (9). It is possible that the effects of v-3 fatty acids on protein turnover are independent of its effects on inflammatory pathways, as suggested in previous studies (4,20). Since we hypothesized that the beneficial effects would be mediated though inflammatory pathways, lower CRP concentrations in the intervention arm at baseline could have led to a reduced effect of fish oil supplementation on protein breakdown.…”
Section: Discussionsupporting
confidence: 62%
“…mostraron un efecto potenciador sobre la fuerza muscular máxima al combinar suplementación de O3 y entrenamiento de resistencia muscular durante 12 semanas. Ellos atribuyeron el aumento de fuerza muscular a los efectos positivos del O3 sobre la permeabilidad de membrana y aumentos en la sensibilidad de acetilcolina (23). La fluidez de membrana aumentaría la velocidad de conducción y facilitaría el impulso nervioso, favoreciendo la contracción muscular.…”
Section: Efectos De La Suplementación De Omega-3 Y Entrenamiento De Iunclassified
“…Another study found grip strength was positively related to fish intake in olderaged men and women and an intervention found fish oils enhanced strength training in men (140,141) .…”
Section: Biological and Behavioural Factors Affecting Loss Of Muscle mentioning
confidence: 99%